Developing “Aryan:” Diabetes self-care mobile application - Maryam Jahanbakhsh; Asghar Ehteshami; Shekoufeh Afkhami (International Journal of Preventive Medicine, 2019)
Background: Diabetes as a chronic and progressive disease leads to multiple complications. Therefore, it is important to control and treat it. More effective control of this condition and the provision of therapeutic approaches require awareness and active participation of patients in self-care. In this regard, a smartphone that is accessible to most people at anytime and anywhere and is easily applicable can be useful in self-care diabetes, with the ability to install various applications. This study aimed to develop a diabetes self-care mobile application as a suitable solution for self-managing diabetes for Iranians. Methods: We conducted a mixed methods study in three Phases: (1) comparative study of existing mobile applications; (2) developed its object-oriented conceptual model; and (3) developed the initial version of “Aryan” that was approved for production. Results: This application was designed for the appropriate diabetes self-care, with following functionalities: The user ID and his/her personal page setting; generating self-care reports such as blood glucose, nutrition, physiological indicators, physical activities, and patient history reports; care setting; providing patient training materials; nutrition control; insulin and other medications control; blood glucose and key tests control; and other paraclinical tests. Conclusions: “Aryan” has been designed in compliance with Iranian experts' opinions. It is expected “Aryan” plays an effective role in self-care of patients with diabetes.